LITERASI TEORETIK TEKNOLOGI VISUAL DALAM PEMBELAJARAN - Idris, Syarifuddin; Lambogo, Bunga Lili Syam (MEDIOVA: Journal of Islamic Media Studies, 2024)
The aimed of this paper is to know how to conduct visual technology in learning process. This paper uses literature review through book review, journal review and relevant research result. The results of the analysis indicate that the used of visual technology can embed student’s interest and provide a relationship between the content of the subject matter with the real world. Several design principles need to be considered, including the principles of simplicity, cohesiveness, emphasis, and balance.